ANALYSING HUGH GLASS’S REVERSE MIMICRY OF NATIVE AMERICAN CULTURE IN FILM THE REVENANT (2015) - Yansa, Muhammad Akbar Malvin Kymy; Koiri, Much.; Sunardi, Dono; Mahamu, Suhaila (CALL, 2025)
Mimicry generally entails the colonized emulating the culture of the colonizer. In The Revenant (2015), the notion of mimicry is inverted, with the colonizer emulating the colonized. While prior research indicated that reverse imitation serves as a subtle method for colonizers to exert their dominance, the analyzed film demonstrated the contrary. This study employs a textual film analysis to scrutinize the film's visual composition, character representation, and symbolic imagery through Homi K. Bhabha's concepts of mimicry and ambivalence. It concludes that Glass's imitation of Native American survival practices, including the consumption of raw flesh and the use of natural remedies, symbolizes his negotiation between colonial identity and reliance on the culture of the colonized. This study underscores how reverse mimicry complicates colonial hierarchies and identity formation within postcolonial film studies.